World's End: A Story in Three Books - Jefferies, Richard, 1848-1887 (Salt Lake City, UT : Project Gutenberg, 2011)
"World's End: A Story in Three Books" by Richard Jefferies is a novel written in the late 19th century. The narrative appears to delve into themes of societal structure and personal ambition through the lens of a developing city and its inhabitants. Central to the plot is the evolution of Stirmingham, a city with a dubious start attributed to a water-rat, and various characters that seem to reflect the struggle between poverty and the quest for wealth and status. The opening of the story introduces the origin of Stirmingham, revealing its transformation from a barren marsh caused by the burrowing activities of the water-rat to a bustling city. Mr. Sibbold, a miserly farmer, and his two sons are introduced alongside the basket-makers who inhabit the swamp, setting up a tension that hints at themes of conflict over land and resources. As Old Sibbold's attempts to reclaim what he believes is rightfully his unfold, the dynamics between the established villagers and the squatters grow complicated, foreshadowing conflict and possibly crime. The groundwork for a rich tapestry of characters and societal critique is established, suggesting a story ripe with drama and moral dilemmas. (This is an automatically generated summary.)
Release date is 2011-08-14
Nick Hodson
Keywords: Inheritance and succession -- Fiction; England -- Fiction; Murder -- Fiction